Student engagement in the Lithuanian EFL classroom - Daukšaitė-Kolpakovienė Aurelija (Nastava i Vaspitanje, 2025)
This article presents the results of a qualitative and quantitative study that used an online questionnaire to research Lithuanian university EFL students' (N=34) self-perceived engagement. It assesses the role of engagement in the EFL classroom through the following research questions: 1) what engages students studying English as a foreign language? 2) what disengages students studying English as a foreign language? 3) how do students describe their own engagement while learning English as a foreign language? Using quantitative and thematic analysis, the findings suggest that the students are engaged by classroom activities (mostly speaking), long-term personal goals, classroom atmosphere, their own mood, and other factors that may differ from student to student. Disengagement is mostly caused by early lecture time, students' laziness, peers who are late or disturb the class, reading tasks, and homework tasks. The students also reflected on their own engagement while studying English, which helped to see the bigger picture regarding their (dis)engagement, as particular challenges, experienced outside the classroom, could also contribute significantly. The study suggests that in order to make teaching and learning more effective, some changes may be necessary, but it is impossible to implement them without understanding the current situation. Knowing what engages and disengages EFL students can help to meet students' needs, shape their learning behaviour, and adopt more multimodal classroom practices.